2018
DOI: 10.1016/j.cbi.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone induces apoptosis in bladder cancer cell via endoplasmic reticulum stress-dependent mitochondrial pathway

Abstract: Our findings provide the first demonstration of the anticancer effect of TQ on bladder cancer, and the relationship between ER stress and mitochondrial dysfunction was clearly understood when the apoptosis progressed is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…The mechanisms underlying the activation of caspases by TQ is very much cell type dependent. In bladder cancer cells, it has been shown that TQ induces endoplasmic reticulum (ER) stress and subsequent action of an ER-stress related signaling pathway leading to mitochondrial dysfunction and caspase 9-mediated activation of caspase 3 [108]. In leukemia-derived HL60 cells, TQ activates caspase 3 via the upstream caspase 8 and mitochondrial release of cytochrome c [105].…”
Section: Induction Of Apoptotic Cell Death In Cancer Cells By Tqmentioning
confidence: 99%
“…The mechanisms underlying the activation of caspases by TQ is very much cell type dependent. In bladder cancer cells, it has been shown that TQ induces endoplasmic reticulum (ER) stress and subsequent action of an ER-stress related signaling pathway leading to mitochondrial dysfunction and caspase 9-mediated activation of caspase 3 [108]. In leukemia-derived HL60 cells, TQ activates caspase 3 via the upstream caspase 8 and mitochondrial release of cytochrome c [105].…”
Section: Induction Of Apoptotic Cell Death In Cancer Cells By Tqmentioning
confidence: 99%
“…ER stress exacerbates mitochondrial dysfunction by activating caspase-9 and increasing the release of cytochrome c [18]. CHOP, DNA damage inducible gene 153 (GADD153), is the main apoptotic factor activated by ER stress, and its overexpression promotes apoptosis in cancer [19].…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Previous studies have confirmed that caspases and Bcl-2 family proteins, such as Bax and Bcl-2, serve important roles in the mitochondrial apoptotic pathway. [36][37][38] Mortenson et al 39 demonstrated that bortezomib triggered cell apoptosis in small cell lung cancer via decreasing Bcl-2 levels. The results of the present study revealed that nitroxoline markedly decreased the level of Bcl-2, and increased the levels of Bax, cleaved PARP and cleaved caspase-3 in a concentration-dependent manner in H929 and RPMI8226 cells.…”
Section: Discussionmentioning
confidence: 99%